Analysis of Consumer Satisfaction and Strategy of Product Attributes Development of Artisan Brie Cheese at PT Rumah Keju Jogja - Pratiwi, Liana Fatma Leslie; Kafiya, Maftuh; Rosyid, Ali Hasyim Al; Utami, Heni Handri (Jurnal Dinamika Sosial Ekonomi, 2025)
Brie cheese is a soft cheese that uses bacteria and fungi as cheese-forming microbes that create a distinctive taste, aroma and texture compared to other cheeses. This study aims to determine consumer characteristics, analyze consumer satisfaction and the strategy for developing brie cheese product attributes at PT Rumah Keju Jogja. The basic method used is descriptive analysis. The location of the study was taken using purposive sampling by selecting PT Rumah Keju Jogja, one of the natural cheese producers in the Special Region of Yogyakarta, with products and services offered in the form of artisan cheese and cheese-making training. The respondents of this study were 80 people who used voluntary sampling techniques. The data analysis method used to determine consumer characteristics is descriptive analysis, which analyses consumer satisfaction using the Customer Satisfaction Index (CSI) method and product attribute development strategies using the Important Performance Analysis (IPA) matrix. The results of the study showed that the characteristics of brie cheese consumers who were respondents were the majority aged 26-35 years, had a bachelor's degree, worked as housewives, and had a household income of more than IDR 7,000,000. Consumers are satisfied with the attributes of brie cheese products. However, to increase consumer satisfaction, an attribute development strategy needs to be implemented, namely by improving product attributes, namely taste, nutrition, preservatives and Halal certification, as well as maintaining performance by maintaining the attributes of aroma, price, shelf life, BPOM permits, and product information.